Crystallographic phase and orientation analysis of GaAs nanowires by ESEM, EDS, TEM, HRTEM and SAED - Tonejc, Anđelka; Gradečak, Silvija; Tonejc, Antun Bijelić, Mirjana; Posilović, Hrvoje Bermanec, Vladimir; Tambe, Michael (2008)
The novel properties of semiconductor nanowires are interesting [1] for application and could be useful for application in nanoelectronics and photonics. Depending on the band gap and size of particular semiconductor nanowires, the shift in absorption/emission is observed. The samples were grown by general synthetic method developed by the C.M. Lieber group [2]. The method controls both the diameter and the length of nanowires (NW) during growth. This approach uses monodisperse nanocluster catalysts Au to define both the nanowire diameter and initiation of nanowire elongation during growth by a vapour– liquid-solid mechanism. In this article, as prepared GaAs NW samples, grown on GaAs [100] and [111] oriented films were synthesized using gold nanocluster catalyst and metalorganic chemical vapour deposition. Figure 1a shows ESEM photographs of NW vertically grown on GaAs [111] oriented film. It is the region from the edge of the sample to measure distribution of the NW lengths (Figure 1b) and the distribution of catalytic gold particles displayed in Figure 1c. The diameter of the catalytic particles at the top of the NW of diameter (94&plusmn ; 20) nm, that had to be the same as NW diameter. Belonging EDS spectrum (Figure 1d) shows the presence of Ga, As and Au. Figure 2a shows NW of GaAs observed by ESEM and EDS grown on [111] films. In Figure 2c TEM image of NW having diameter d= (32 &plusmn ; 10) nm, measured from TEM, is shown. The corresponding SAED in [111] Au orientation of the catalytic particles shows HCP spots as well as the  001 GaAs. The SAED (Figure 2d) gives evidence that the substrate film had the same orientation. The growth direction of NW is [011] and the structure is identified as HCP GaAs, according to ICDD-PDF No. 80-0003. The distribution of the lengths of nanowires is given from 500 to 3500 nm with maximum values 1300 and 2000 nm, for two observed samples, Figure 1c and Figure 2b , respectively. From HRTEM images it is found that NWs are coated with 3 to 5 nm thick amorphous layer. 1. M. Law, J. Goldberg and P. Yang, Annu. Rev. Mater. Res. 34 (2004), p. 83. 2. Y. Cui, L.J. Lauhon, M.S. Gudiksen, J. Wang and C.M. Lieber, Applied Physics Letters 78 (2001), p. 2214.
Projekt MZOS
ENG